High-intensity interval training may reduce depressive symptoms in individuals with schizophrenia, putatively through improved VO2max: A randomized controlled trial - Bang-Kittilsen, Gry; Engh, John Abel; Holst, René; Holmen, Tom Langerud; Bigseth, Therese Torgersen; Andersen, Eivind; Mordal, Jon; Egeland, Jens (Frontiers in Psychiatry, 2022)
Introduction: High-intensity interval training (HIIT) may improve cardiorespiratory fitness and mental health. The current observer-blinded RCT investigates the sparsely studied efficiency of HIIT in reducing psychotic and non-psychotic symptoms in schizophrenia, and complement previous studies by investigating whether symptom reduction following HIIT is associated with, putatively partly mediated by, increased VO2max. Methods: Participants (outpatients meeting diagnostic criteria for schizophrenia) were randomized to HIIT (n=43) or a comparison-group performing low-intensity active-video-gaming (AVG) to control for social interaction (n=39). Both interventions consisted of 2 supervised sessions/week for 12 weeks/ 4 months follow-up. Effects on overall-symptoms and symptom-domains (PANSS (0-6 scale), five-factor model) were estimated using mixed-effects models (intention-to-treat, n=82). Underlying mechanisms were analyzed using moderated mediation-analyses (n=66). We anticipated that HIIT would reduce overall-symptoms, and in particular depressive symptoms, more than AVG, and symptom-reduction would be associated with, putatively mediated through, improved VO2max.. Results: Depressive symptoms, baseline-score 3.97 (95%CI 3.41,4.52), were more reduced in HIIT at post-intervention, -1.03 (95%CI -1.71,-0.35), p=0.003, corresponding to a small to moderate effect-size (d=0.37), and persisting at follow-up. There was a small reduction in overall-symptoms, but no significant between-group difference. Change in VO2max correlated negatively with change in depressive symptoms. Mediation-analysis showed a significant effect of change in VO2max on change in depressive symptoms within HIIT. Total effect was moderated by group, and depressive symptoms were more reduced in HIIT. Direct effects, not mediated through VO2max, were non-significant. Indirect effects, mediated through VO2max, were non-significant, but the moderated mediation test indicated a non-significant trend of 0.4 point (95% CI -1.188, 0.087) larger reduction in depressive symptoms through VO2max in HIIT. Conclusions: HIIT reduced depressive symptoms more than AVG, persisting at follow-up. HIIT may serve as a complementing treatment-option targeting these symptoms in individuals with schizophrenia, also before they reach clinical depression. Depressive symptoms are important to prevent, stabilize and treat due to their negative implications for psychological well-being and long-term functional outcome. Reduction in depressive symptoms was associated with improved VO2max, and non-significant trends in the data supported that improved VO2max may be part of the complex mechanisms underlying the anti-depressive effect of HIIT. NCT02205684.